Interaction of Organogermanium Compounds with Saccharides in Aqueous Solutions: Promotion of Aldose-to-ketose Isomerization and Its Molecular Mechanism - Nagasawa, Takae; Sato, Katsuyuki; Kasumi, Takafumi (Journal of applied glycoscience : JAG, 2023)
This review discusses sugar isomerization with organogermanium compounds. Organogermanium compounds markedly increase the aldose-ketose (glucose-fructose or lactose-lactulose) isomerization ratio, double the initial reaction rate, and significantly reduce the base-catalyzed degradation of sugars. 1H-nuclear magnetic resonance analysis reveals that the affinity of organogermanium compounds with a 3-(trihydroxygermyl)propanoic acid (THGP) structure toward ketoses is 20-40 times stronger than that toward aldoses; thus, such organogermanium compounds form complexes more readily with ketoses than with aldoses. Stable ketose complexes, which contain multiple cis-diol structures and high fractions of furanose structures, suppress the reverse ketose-aldose reaction, thereby shifting the equilibrium toward the ketose side. These complexes also protect sugar molecules from alkaline degradation owing to the repulsion between anionic charges. The increased rate of the initial reaction in the alkaline isomerization process results from stabilizing the transition state by forming a complex between THGP and a cis-enediol intermediate. The cyclic pentacoordinate or hexacoordinate THGP structures give rise to a conjugated system of germanium orbitals, which is extended through dπ-pπ interactions, thereby improving the stability of the complex. Based on these results, we have developed a bench-scale lactulose syrup manufacturing plant incorporating a system to separate, recover, and reuse organogermanium poly-trans-[(2-carboxyethyl)germasesquioxane]. This manufacturing plant can be used as a model of an alkaline isomerization accelerator for continuous industrial production.